Gambaran Karakteristik Pengetahuan Ibu yang Memiliki Balita dengan ISPA di Puskesmas Siliwangi Garut - Sandra Pebrianti; Iwan Shalahuddin (Jurnal Medika Cendikia, 2018)
ISPA (Upper Respiratory Tract Infection) is a health problem that often occurs in the community especially in infants, toddlers and children, this is a reflection for all of us that to realize a high degree of health is not easy. Infection of the acute respiratory tract. Knowledge is the result of knowing and this happens after someone has sensed a certain object. Sensing occurs through the five human senses, namely the senses of sight, smell, taste, touch, and taste. Most human knowledge is obtained through the eyes and ears. Objective To find out "Overview of Knowledge of Mothers Who Have Toddlers about ISPA Based on the Characteristics at the Siliwangi Health Center in Garut. Sample Population A total of 20 respondents from those who visited the Puskesmas for three days. The results show that the age of respondents who have good knowledge is the young age with the average level of education in senior high school and those who get information from electronic media. The conclusion is that the younger the age and the more diligent search for information can increase public knowledge.